Hands-on instruction: the iPad self-guided library tour. Issue 2 (8th June 2015) - Foley, Marianne; Bertel, Katherine
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe how librarians at the State University of New York College at Buffalo used iPads during one class session of a semester-long library instruction course to increase student engagement, energize the traditional library tour, build collaboration and give students experience using tablet technology in an educational setting. Design/methodology/approach – Librarians provided iPads to groups of students and sent them to photograph different areas of the library during one class session of a semester-long course. Students then uploaded the photographs to a common Web site for class discussion. Findings – Formal and informal student feedback was positive. Students connected with the instructors and with each other, enjoyed discovering library spaces and services and became more comfortable with tablet technology. The project also increased student enthusiasm for the class. Originality/value – This paper is the first to systematically describe a simple activity that can be used by instruction librarians to incorporate tablets into the curriculum. The method requires minimal time to set up and implement, involves a very short learning curve and is easily adaptable to various mobile devices.